Building a Structure for Adopting Green-Lean Construction Techniques (International Journal of Innovative Research in Engineering & Management, 2021)
Traditional construction methods commonly produce waste and  contribute to the environment's pollution. This study aims to  develop a framework that will integrate green building techniques  into the construction sector. The Analytical Network Process  (ANP) and Zero One Goal Programming(ZOGP) were used to  lead the overview .The outcomes recommended a decent  arrangement to accomplish a practical green reliance system; this  incorporates numerous mediations that can be utilized to move  customary development to green development. The review  reasoned that voyaging greenlings are more affordable whenever  utilized effectively. The results of the survey indicated that a good  plan should be developed to implement a green dependence  framework. This framework should include various interventions  that can help minimize the cost of green construction. Doing  business around can save you time and money while improving  the safety and cleanliness of buildings. It is also a good idea to  consider new forms of energy and water conservation. It can also  help minimize energy use and costs. It can also help avoid costly  mistakes and doing so can also help minimize air pollution.
Keywords: Analytical Network Process; Green techniques; Lean construction; Green buildings; ANP; ZOGP